VD_FINDINFO Pron / 2013 / 228 vom 5. September 2013 - VD Tribunal cantonal (2013)
PROTECTION DE L'UNION CONJUGALE, TRANSACTION JUDICIAIRE | 105 al. 1 CPC (CH), 109 CPC (CH), 241 al. 2 CPC (CH), 241 al. 3 CPC (CH)